2018
DOI: 10.1007/s00590-018-2144-8
|View full text |Cite|
|
Sign up to set email alerts
|

Uncemented Thompson’s hemiarthroplasty: safe, palliative and cost-effective surgery in the infirm patient—a consecutive series of 1445 cases

Abstract: Current guidelines strongly favour cemented hemiarthroplasty. Recognition that fractured hip patients are a non-homogeneous group is important. In patients with limited life expectancy, an uncemented Thompson is a quick, simple, palliative solution to early mobilisation. Correct surgical technique avoids using cement in this cohort, which is most vulnerable to bone cement implantation syndrome. Cost-effective resource utilisation with an increasingly elderly population remains a surgical responsibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…22 Conversely, Manoharan et al found cemented hemiarthroplasty to cost £501.42 (British Pound, equivalent to about US$648) more on average than press-fit hemiarthoplasty. 23 Tripuraneni et al similarly determined cemented constructs were US$418.87 more expensive than cement-less constructs. 24 However, this study was underpowered, including a small number (N = 94) of participants operated on by only 2 surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…22 Conversely, Manoharan et al found cemented hemiarthroplasty to cost £501.42 (British Pound, equivalent to about US$648) more on average than press-fit hemiarthoplasty. 23 Tripuraneni et al similarly determined cemented constructs were US$418.87 more expensive than cement-less constructs. 24 However, this study was underpowered, including a small number (N = 94) of participants operated on by only 2 surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies have addressed the long-term outcomes of elderly patients with low-energy fractures treated with HA, however, given the current situation in many developed countries (i.e., aging populations), this issue now urgently demands attention. Two implant fixation techniques exist (i.e., cemented, cementless) and in the short term, both techniques are reported to have comparable functional results5678). Cemented HA is reportedly associated with: i) less thigh pain910), ii) better mobility11), and iii) a lower frequency of periprosthetic fractures61213).…”
Section: Introductionmentioning
confidence: 99%